2023
DOI: 10.1177/20552076231186069
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of a machine learning-based lower-limb exercise training system among older adults with knee pain

Abstract: Objective To facilitate the older adults with knee pain to perform exercises and improve knee health, we proposed the design of a machine learning-based system for lower-limb exercise training that features three main components: video demonstration of exercises, real-time movement feedback, and tracking of exercise progress. At this early stage of design, we aimed to examine the perceptions of a paper-based prototype among older adults with knee pain and investigate the factors that may influence their percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“… 48 A study of the perceptions regarding machine learning-based lower-limb exercise training in older adults with knee pain revealed that they were satisfied with the system's ease of use. 49 In a survey on Qigong Training app use for feedback and learning outcomes, participants indicated that the apps were pleasant to use and useful for learning. 50 Although we conducted an intervention study, we did not assess the participants’ feelings toward the intervention.…”
Section: Discussionmentioning
confidence: 99%
“… 48 A study of the perceptions regarding machine learning-based lower-limb exercise training in older adults with knee pain revealed that they were satisfied with the system's ease of use. 49 In a survey on Qigong Training app use for feedback and learning outcomes, participants indicated that the apps were pleasant to use and useful for learning. 50 Although we conducted an intervention study, we did not assess the participants’ feelings toward the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the implementation of other healthcare technologies, their usability, acceptance, and effects on knee health are worth further investigation among the end users. 33 – 39…”
Section: Discussionmentioning
confidence: 99%
“… 20 26 Moreover, users’ perceptions of a technology, such as its ease of use and usefulness, can influence their attitudes toward the technology and ultimately impact their acceptance of the technology. 8 , 27 39 In the context of the use of technology in poststroke motor rehabilitation, stroke patients’ perceptions of VR-based rehabilitation programmes can also influence their acceptance of and adherence to the programmes; however, research on this topic has been limited.…”
Section: Introductionmentioning
confidence: 99%